COVID-19 patients with progressive and non-progressive CT manifestations - Tan, Yiqing (Radiol Infect Dis, 2020)
OBJECTIVE: To explore the clinical and radiological characteristics of COVID-19 patients with progressive and non-progressive CT manifestations. METHODS: 160 patients with COVID-19 were retrospectively included from Wenzhou and Wuhan, China. CT features including lesion position, attenuation, form and total scores (0–4) at the segment level were evaluated. Other images signs were also assessed. 65 patients were classified as progressive (Group 1) and 95 as non-progressive CT (Group 2) groups according to score changes between the initial and second CT. RESULTS: Symptoms onset-initial CT interval time in group 1 [5 (2, 7) days] were significantly shorter than that in group 2 [10 (8, 14) days] (P < 0.001). Group 2 had higher radiological scores, with more lobes and segments affected, and other CT signs (P < 0.05). In group 1, radiological scores, the number of lobes and segments affected as well as lesions in both peripheral and central distribution, mixed ground grass opacity and consolidation density, and patchy form increased in the second CT (P < 0.05). More reticular pattern, subpleural linear opacity and bronchial dilatation were also found (P < 0.05). CONCLUSION: Typically radiological characteristics of progressive CT patients could potentially help to predict changes and increase understanding of the natural history of COVID-19.